Crowning achievement: a case of dental aspiration - Nicholas M. Mark, MD; Juan N. Lessing, MD; Başak Çoruh, MD (Radiology Case Reports, 2015)
Aspiration of foreign bodies during dental procedures is a rare but potentially serious complication. We present a case of a 75-year-old man who aspirated a dental crown requiring flexible bronchoscopic retrieval. We discuss the risk factors for aspiration, the radiographic features of diagnosis, and the techniques for management and retrieval.